2018
DOI: 10.1111/ppc.12269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatitis C infection on the quality of life

Abstract: QoL is lower for patients who are older, female, and have depressive symptoms. Progression of hepatic cirrhosis is associated with lower QoL in the physical domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
1
0
2
Order By: Relevance
“…Some studies have indicated that hepatitis can cause fatigue and reduced feeling. Mallolas et al [27] revealed that the life quality of patients with hepatitis C is worse than that in the healthy control group, which agrees with other studies [28,29].…”
Section: Resultssupporting
confidence: 68%
“…Some studies have indicated that hepatitis can cause fatigue and reduced feeling. Mallolas et al [27] revealed that the life quality of patients with hepatitis C is worse than that in the healthy control group, which agrees with other studies [28,29].…”
Section: Resultssupporting
confidence: 68%
“…The patient population consisted of patients with autoimmune or cholestatic liver disease (19 studies), [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] chronic hepatitis B or C (35 studies), [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] NAFLD or NASH (15 studies), [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , …”
Section: Resultsunclassified
“… 9 , 12 , [22] , [23] , [24] , [25] , [26] Mental, physical, and social factors, such as body composition, comorbidities, fatigue, lack of information on the disease, and low income together with patient characteristics, such as younger age at diagnosis, alcohol use, and female sex, were associated with impaired quality of life. 8 , 10 , 11 , 15 , 18 , 21 , 30 , 33 , 35 , [42] , [43] , [44] , 48 , 49 , 58 , 59 , 66 , 67 , 72 , 74 …”
Section: Resultsmentioning
confidence: 99%
“…Многочисленные исследования установили, что качество жизни больных хроническими вирусными гепатитами снижено, как по физическому, так и по психологическому компонентам здоровья [5,6]. У таких пациентов выявлено ухудшение основных показателей качества жизни на стадии обострения заболевания [7,8].…”
unclassified